1977
DOI: 10.1063/1.89305
|View full text |Cite
|
Sign up to set email alerts
|

Sodium passivation in HCl oxide films on Si

Abstract: Chlorine has been incorporated into SiO2 films by thermal oxidation of Si in a mixture of O2 and HCl gases. Mobile sodium ions adsorbed on the oxide surface were drifted to the Si-SiO2 interface (0.5 MV cm−1 bias at 200 °C). Passivation, defined as the fraction of mobile sodium charge neutralized, exhibited a pronounced threshold with HCl content in the growth ambient. This was partly due to a similar variation of oxide chlorine content (measured by α-particle backscattering). For fixed growth temperature, pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…A higher steadystate broken-bond density is obtained both within the oxide film and within the transition region. Intermediates such as St-C1, which have bond energies only 0.7 eV less than Si-O (4.7 eV), are detected within the first 200A of the oxide film (38). Oxidation kinetics are also enhanced at the SiO2-Si interface (37).…”
Section: St-st + H~o -> Si-h + St-oh [2]mentioning
confidence: 99%
See 1 more Smart Citation
“…A higher steadystate broken-bond density is obtained both within the oxide film and within the transition region. Intermediates such as St-C1, which have bond energies only 0.7 eV less than Si-O (4.7 eV), are detected within the first 200A of the oxide film (38). Oxidation kinetics are also enhanced at the SiO2-Si interface (37).…”
Section: St-st + H~o -> Si-h + St-oh [2]mentioning
confidence: 99%
“…The second oxidation reaction step involving oxygen as oxidant is the thermally activated reaction in which siloxane groups are formed as is shown in [5] _=St-+ (St-O) + + e--> St-O-St [5] In reaction [5], (St-O)+ complexes react at typical oxidation temperatures with incompletely oxidized Si atoms such as --St., as shown above, or with St-St bonds. Restructuring, or the displacement of Si atoms from their original lattice sites during this thermal oxidation reaction, can occur at three levels: at the substrate surface, within the transition region, and within the oxide film where bond angles are modified to accommodate newly formed oxide film (38). This reaction is exothermic and leads to a stable siIoxane structure.…”
Section: St-st + H~o -> Si-h + St-oh [2]mentioning
confidence: 99%
“…Coincidentally increased oxidation rates have been observed with increasing chlorine concentration in the oxygen ambient (1)(2)(3)(4). The reported improvements in device properties are probably due in part to actual incorporation of a chlorine species in the silicon oxide and reaction of this species with impurities (8,9). It has been proposed that the increased oxidation rates are due either to the reaction products (such as I-t20 and C12 from 02 plus HC1) or the effect of the chlorine species itself on the oxide growth mechanism, or both (1)(2)(3)(4).…”
mentioning
confidence: 97%
“…Previous reports [1,2] have shown that partial or complete neutralization of the Na+ at the Si-Si02 interface can occur in these oxides. It is known [1,3] that the neutralized ions are trapped much more strongly at this interface than are charged ions in normal dry oxides.…”
mentioning
confidence: 85%